Hydrophobic, structural and optical properties of zinc silica thin films - Aziz, Nur Aimi Syaqilah (2013)
A fundamental study was conducted to investigate the hydrophobic properties, structural characteristics, surface morphology and topology, and luminescence properties of the zinc silica thin films due to various ZnO content. Hydrophobically zinc silica thin films, xZnO-(1-x)SiO2 with 0 < x < 20 wt%, have been prepared using a low temperature sol-gel process and dip coating technique. The hydrophobic properties were determined using contact angle measurement which gave the static water contact angle of 102 ± 1° for 20 wt% of ZnO. The structural characteristics were investigated using Infrared (IR) Spectroscopy in the range of 400 – 4000 cm-1. The peaks observed on the spectra showed the C-H, C-H3, Si-O-Si, Si-O-Zn and Zn-O bonding. The changes in morphology and topology were characterized by Atomic Force Microscopy (AFM) and Field Emission Scanning Electron Microscopy (FESEM). The surface roughness of the hydrophobic coatings showed a maximum value of 148.32 nm while the maximum size of the pores was found to be 6.47 µm. The optical absorption and photoluminescence properties were studied by means of UV-Visible optical absorption and Photoluminescence (PL) spectroscopy. All samples exhibited more than 90 % optical transmittance which indicated a higher transparency of the films. The emission spectra showed broad and sharp peaks of luminescence at 390, 420, 550 and 740 nm corresponding to the characteristic of Zn2+ due to transitions of 2S1/2?2D5/2, 2S1/2?2D3/2, 2D3/2?2P°3/2 and 2D5/2?2P°3/2, respectively. The thin films prepared in this work have shown to be promising materials for use in hydrophobic and water-resistant applications.